Pump-probe microscopy of tailored ultrashort laser pulses for glass separation processes - Jenne, Michael; Flamm, Daniel; Faber, Max; Grossmann, Daniel; Kleiner, Jonas; Zimmermann, Felix; Kumkar, Malte; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
The confined and tailored interaction of ultrashort laser pulses with wide band-gap materials such as glass led to a broad range of applications and processing methods throughout recent years, especially for glass cutting. One major benefit of the short pulse duration is to locally modify a defined area inside of the glass volume. By stringing together numerous modifications along a desired contour, a preferential separation path can be created. However, complex contours and the extension to glasses of several millimeters thickness remain a challenging task due to the generation of cracks with undesired orientation, which antagonize the preferred separation direction. This might result in a loss of quality and stability due to rough cutting surfaces or even a lack of separability. A prominent example for single pass cutting profiles are Bessel-like beams. Their elongated but transversally confined intensity profile facilitate the homogeneous modification on a millimeter length-scale. Moreover, advanced beam shaping enables laterally anisotropic beam shapes leading to a preferential direction for crack propagation and allows to further increase the quality and process management. We employ pump-probe microscopy to study the effect of the interaction of single and multiple laser pulses. The combination of transmission microscopy, polarization microscopy and cutting processes under observation for time delays up to several microseconds allows the in situ detection of pressure waves and transient stress. Camera recording rates in the 100 kHz range allow the continuous detection of stress- and crack-formation and eliminate stochastic uncertainties. In combination with multipulse experiments and glass samples under feed rate, a profound understanding of cleaving applications is achieved.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Imaging ultrafast phenomena; Ultrafast lasers; Ultrafast optics; Ultrafast processing